1979
DOI: 10.1159/000119832
|View full text |Cite
|
Sign up to set email alerts
|

Klippel-Feil Syndrome, Iniencephalus, Anencephalus, Hindbrain Hernia and Mirror Movements

Abstract: Bony anomalies encountered in the ‘no neck’ form of Klippel-Feil syndrome (KFS) are a wide, short, fused, bifid, retroflexed spinal canal; craniolacunia, cranium bifidum, and acrania. The only symptom may be mirror movement (MM). The CNS anomalies are hindbrain hernia, hydrocephalus, hydromyelia, syringomyelia, meningocele, myelocele, encephalocele, and anencephalus. In severe KFS, i.e. iniencephalus (IN) and in anencephalus (AN), the inion is in contact with the back. In both there is hindbrain hernia and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
3

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 2 publications
1
21
0
3
Order By: Relevance
“…4 The time of onset is likely a little after that of anencephaly. 5 The two main iniencephaly groups were first described by Lewis: iniencephaly apertus, which has an encephalocele, and iniencephaly clausus, which has a spinal defect but no cephalocele. 1 The main features of iniencephaly include a variable deficit of the occipital bones that results in an enlarged foramen magnum; partial or total absence of cervical and thoracic vertebrae with irregular fusion of those present, and incomplete closure of the vertebral arches and bodies; marked reduction of the spinal column due to lordosis and hyper-extension of the malformed cervicalthoracic spine; and an upward-turned face with mandibular skin that is directly continuous with that of the chest, owing to the lack of neck.…”
Section: Discussionmentioning
confidence: 99%
“…4 The time of onset is likely a little after that of anencephaly. 5 The two main iniencephaly groups were first described by Lewis: iniencephaly apertus, which has an encephalocele, and iniencephaly clausus, which has a spinal defect but no cephalocele. 1 The main features of iniencephaly include a variable deficit of the occipital bones that results in an enlarged foramen magnum; partial or total absence of cervical and thoracic vertebrae with irregular fusion of those present, and incomplete closure of the vertebral arches and bodies; marked reduction of the spinal column due to lordosis and hyper-extension of the malformed cervicalthoracic spine; and an upward-turned face with mandibular skin that is directly continuous with that of the chest, owing to the lack of neck.…”
Section: Discussionmentioning
confidence: 99%
“…2 Other proposed theories include overdistention of the neural tube resulting in distortion of the somites and reduced expressivity of the Hox or Pax genes, the highly conserved DNA sequences that control the development of the intervertebral disks. 8 A mechanical basis to explain the relationship between these abnormalities is that during the formation of the cephalic and cervical brain flexures, a shortening of the cervical spine because of a reduction or fusion in the number of somites may result in altered tissue tension, which could lead to entrapment of dermal elements. 9 Patients with KFS and posterior fossa dermoid cysts present with a variety of signs and symptoms, which may be attributed to both craniovertebral bony anomalies and increased intracranial pressure secondary to mass effect.…”
Section: Discussionmentioning
confidence: 99%
“…It should be recognized that visceral and neural structures can be involved in this disorder and that the central nervous system may be involved as well. A unifying hypothesis which explains visceral and neural involve ment has been offered by Gardner and co-workers [3][4][5]. In the developing embryo, the central nervous system is first to develop and it serves all emerging structures during embryonal development.…”
Section: Discussionmentioning
confidence: 99%
“…The injury to the neural structures was suggested to be of primary pathogenetic significance [4], The presence of numerous spinal column anomalies including Klippel-Feil anomaly in case I as well as hemivertebrae and other anom alies of the spinal column in case 2 are of interest. It was suggested that bony anomalies of the spinal column and limb hypoplasia are the result of the rupture of the neural tube [3,4], The normal spinal cord in case 1 argues against it. The anomalies of the spinal cord in case 2 could result in hypoplasia of the corresponding limb.…”
Section: Discussionmentioning
confidence: 99%